Pengaruh Work Life Balance dan Gaya Kepemimpinan Terhadap Kinerja Pegawai pada Sekretariat Daerah Kabupaten Tangerang - Savera Maharani; Furi Indriyani; Rohani Lestari Napitupulu (Teewan Journal Solutions, 2026)
The Regional Secretariat (SETDA) of Tangerang Regency is a government institution under the coordination of the Regional Secretary and directly accountable to the Regent. This study aims to examine the extent to which work-life balance and leadership style influence employee performance. The research employs a quantitative statistical approach, with data collected through observation, questionnaires, and documentation studies. The study population consists of 162 employees, from which a sample of 62 was determined using the Yamane formula. The sampling technique applied is simple random sampling, which selects respondents randomly without considering levels or strata within the population. This study applies data quality tests, classical assumption tests, hypothesis testing, multiple linear regression analysis, and the coefficient of determination test using SPSS version 26. The variables examined include work-life balance and leadership style as independent variables, while employee performance serves as the dependent variable. The results show that, partially, work-life balance has a positive and significant effect on employee performance, and leadership style also has a positive and significant effect on employee performance. These findings confirm that maintaining a balance between work and personal life, combined with applying an appropriate leadership style, can serve as an optimal strategy to enhance employee performance within the Regional Secretariat of Tangerang Regency.